The Effect of Microscope Skills On The Observation Results Of Plant Tissue Preparations by Students Of SMAN 4 Tegal - Fajarini, Nata Maulida; Peniati, Endah; Abdullah, Muhammad (FMIPA UNNES, 2020)
Microscope skills is a skill that should be managed by the students in the laboratory works with a microscope. This research aimed to determine the effect of microscope skills on the observation results of plant tissue preparation by students of SMAN 4 Tegal. This is a Quasi Experimental research with Intact-Group Comparison design. Sample divided into three groups: (1) XI MIA 5 was given demonstration and microscopes instructions sheet; (2) XI MIA 4 was given microscopes instructions sheet only; and (3) XI MIA 2 neither given demonstration nor microscopes instructions sheet. The results of this research showed that the signification value of ANOVA test both on the microscope skills grades and observation result grades that was 0,000<0,05, which mean there was a average different grade between three group treatments. Furthermore, significance value of simple linear regression test was 0,000<0,05, which mean microscope skills affected the observation results. The raise of microscope skills grades followed by the raise of observation result grades. Correlation coefficients value (R) was 0,939 showed a very strong correlation and adjusted R square value (R2) was 0,881 showed microscope skills affected the observation results for 88,1%. Therefore, it can be concluded that microscope skills positively affected the observation results of plant tissue preparation by students of SMAN 4 Tegal.